Development of tapered optical fiber-based sensor for detection of dengue II e proteins - Mustapha Kamil, Yasmin (2018)
The escalating cases of dengue around the globe has become a major public health concern with an estimation of 300 million infections, annually. Due to the absence of a cure and a narrow time window for successful detection, survival relies heavily on sensitive, reliable, rapid and accurate diagnostics that would facilitate better clinical management and control over the epidemic. The underlying problem in managing the disease heightens when conventional diagnostics that are available today have crucial set-backs impeding efficient surveillance of the disease. For the past decade, tapered single-mode fibers have exhibited versatility and enticing sensitivity towards changes of its surrounding refractive index, making it favorable to be employed in sensing systems. The research work demonstrates the development of label-free tapered optical fiber-based sensor for the detection of dengue II E proteins. The sensing principle lies within the reaction of evanescent waves driven from the tapering of the optical fiber, towards changes within the external surrounding, in which would produce measurable response that enables to determine the concentration of the proteins. To ensure its selectivity, dengue II E protein complimentary antibodies were immobilized onto the surface of the tapered fiber. The proposed setup obtained a comparable sensitivity of 5.44 nm/nM with a detection limit of 1 pM within a short response time. For further performance enhancement of the sensing system, graphene oxide (GO) and polyamidoamine (PAMAM) dendrimer were integrated to promote higher surface to volume ratio, homogenous adhesion and better molecular orientation. The characteristics of these two nanomaterials are expected to increase the sensitivity of the sensor and its affinity towards dengue II E proteins. With both nanomaterials tested individually as enhancement layers onto the tapered fiber, better sensitivity was obtained when compared to the sensitivity obtained before, with values for PAMAM and GO at 19.53 nm/nM and 12.77 nm/nM, respectively. However, when both layers were applied onto the same tapered fiber, the performance of the sensor was not as satisfactory as PAMAM alone, as it only managed to achieve a sensitivity value of 13.25 nm/nM. Noting that optical fibers are inexpensive, flexible, and now has shown promising performance in the detection of the dengue virus, it is anticipated of this work to be the first vital steps towards the development of better dengue diagnostics